Study the morphological charactertics and the effect of foods on development and growth of Ostrinia furnacalis (Guenee, 1854) (Lepidoptera: Pyralidae) - Minh Hong, Bui; Hung, Nguyen Duc; Chien, Tran Dinh (VNU Journal of Science: Natural Sciences and Technology, 2018)
The effects of foods on the life cycle, survival rate , and reproductive ability of Ostrinia furnacalis (Guenee, 1854) were studied in laboratory. Maize HN88-Fed O . furnacalis had a complete life cycle of 32.9 ± 1.7 days, which was 38.4 ± 1.5 days shorter than those fed with maize LVN4. The average survival rates of O . furnacalis on two types of feeds were 97.5% and 94.4%, respectively. When O. furnacalis were fed with 100% honey or 50% sugar or water, the average length of female life cycle as well as their everage laid egg number were 11.1 ± 0.9 days and 535.2 ± 77.2 eggs/female; 9.9 ± 0.8 days and 371.7 ± 47.4 eggs/female; 7.3 ± 0.6 days and 216 ± 32.6 eggs/female, respectively. Keywords The effect of foods on Ostrinia furnacalis References Đặng Thị Dung (2003). Một số dẫn liệu về sâu đục thân ngô (Ostrinia furnacalis Guenee) Pyralidae-Lepidoptera trong vụ xuân 2003 tại Gia Lâm, Hà Nội, Tạp chí BVTV số 6, tr 7-12. [2]. Patanakamjorn Somporn (1975). Biology of the tropical corn borer, Ostrinia furnacalis (Guenee) inrelation to host plant resistance research. Retrospective Theses and Dissertations. 5435 [3]. Đặng Xuân Hưng (2010). Nghiên cứu một số đặc điểm sinh học, sinh thái của sâu đục thân ngô Ostrinia furnacalis Guenee và biện pháp phòng chống vụ đông 2009 và hè thu 2010 tại Gia Lâm, Hà Nội. Luận văn Thạc sỹ Nông nghiệp, Trường Đại học Nông nghiệp Hà Nội 75 trang.11/2010. [4]. Yoshio Hirai and Danilo M. Legacion (1985). Improvement of the Mass Rearing Techniques for the Asiatic Corn Borer, Ostrinia furnacalis (Guenee), in the Philippines. Japan Agricultural Research Quarterly (JARQ) Vol. 19, No. 3, 1985